What Drives Firm Value in Capital-Intensive Industries? Evidence from Energy and Basic Materials Firms in Indonesia and Malaysia - Luthfiani, Anin Dyah; Romadhon, Fitri; Fitri, Alfiana (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2026)
Purpose: This study examines the main factors that influence firm value in capital-intensive industries. Specifically, it analyzes whether firm size, market capitalization, and firm growth affect firm value in Indonesia and Malaysia. Methodology/approach: The study uses a quantitative explanatory approach with panel data from publicly listed energy and basic materials companies in Indonesia and Malaysia during 2021–2024 (n = 171). Panel regression analysis is applied to the full sample and to each country separately to compare the results between the two markets. Findings: The results show that firm size and market capitalization have a positive and significant effect on firm value in both countries and in the combined sample. However, firm growth does not have a significant effect. This indicates that in capital-intensive industries, investors pay more attention to company size and market valuation than to growth indicators. The model explains firm value better in Indonesia than in Malaysia, suggesting differences in how each market responds to company characteristics. Practical implications: For managers, the findings emphasize the importance of increasing company scale, maintaining transparency, and strengthening market reputation to improve firm value. For investors, firm size and market capitalization appear to be more reliable indicators than growth when assessing companies in capital-intensive sectors. Originality/value: This study provides comparative evidence from two Southeast Asian emerging markets and offers empirical support for agency theory by demonstrating how larger firms and stronger market valuation mechanisms can reduce information asymmetry and enhance firm value in capital-intensive environments.